Effects of Anthocyanin Supplementation on Serum Lipids, Glucose, Markers of Inflammation and Cognition in Adults With Increased Risk of Dementia – A Pilot Study - Bergland, Anne Katrine; Soennesyn, Hogne; Dalen, Ingvild; Rodriguez-Mateos, Ana; Berge, Rolf Kristian; Giil, Lasse Melvaer; Rajendran, Lawrence; Siow, Richard; Tassotti, Michele; Larsen, Alf Inge; Aarsland, Dag (Frontiers in Genetics, 2019)
Background Anthocyanins may protect against cardiovascular related cognitive decline and dementia. Objective Open-label study to measure changes in serum lipids, glucose, glycosylated hemoglobin (HbA1c), and markers of inflammation after anthocyanin supplementation in people with increased risk of dementia. As a secondary endpoint we examined potential changes in a battery of cognitive test in the anthocyanin group (AG). A total of 27 individuals with mild cognitive impairment (MCI) (n = 8) or stable non-obstructive coronary artery disease (CAD) (n = 19) consumed two Medox® capsules, each containing 80 mg of natural purified anthocyanins, twice daily for 16 weeks. They provided blood samples and performed a short battery of cognitive tests. Twenty healthy normal controls (NC) (n = 20) provided blood samples, but did not receive any intervention and did not perform cognitive tests. Results There was a significant difference between groups for monocyte chemoattractant protein (MCP-1) and fasting glucose. In addition, total cholesterol and triglycerides were significantly increased in the AG. Improvements in memory and executive test scores were observed. No adverse effects were reported. Conclusion The results of this pilot study were largely inconclusive with regard to the potential protective effects of anthocyanin supplementation. However, anthocyanins were well tolerated, and compliance was high. Larger, placebo-controlled studies to explore the potential effects of anthocyanins on dementia risk are encouraged. Clinical Trial Registration www.ClinicalTrials.gov, identifier NCT02409446